Storytelling - sponsorship communication in sport - Kończak, Jarosław (Quality in Sport, 2018)
Storytelling is in the broadly understood communication, including sponsorship, the art of telling stories that engage customers while distinguishing the brand in a competitive market. It is a tool that does not directly promote products, brands or companies, but promotes ideas, values based on emotions. The last ones are not lacking in sport. And it is on emotions that sponsorship communication is largely based, which eagerly uses the story as part of building the brand’s image.